Kolaborasi Budaya pada Lukisan Tradisional Tiongkok di Indonesia - Ariesa Pandawangi; Belinda Sukapura Dewi (PANTUN, 2019)
Chiang Yu Tie is a female painter recognized with her Chinese painting technique. Few Chinese women are recorded in Indonesia fine art history. Chiang Yu Tie had qualified track record of exhibitionin 1900s.However, her name was not recognizable yet in national fine art. The aim of this research is to equip infrastructure of social fine art area in Indonesia relating to the visualization of Chinese female art works. This research uses qualitative method and case study. This research shows that the local genius of Chiang Yu Tie work can be appreciated through figure of the dancer and panorama collaborated with Chinese traditional painting style. The composition made by Chiang Yu Tieis convergence. This composition is used to state that the object is important. The colors highlighted in her painting are the natural colors such as light green, light brown, light blue, with black outlineas the confi rmation of the highlighted object. Keywords: Chiang Yu Tie, Chinese painting, fine art